2015
DOI: 10.1074/jbc.m115.670018
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Monomeric GTPase Rab1 in the Secretory Pathway of Leishmania

Abstract: Leishmania secretes a large number of its effectors to the extracellular milieu. However, regulation of the secretory pathway in Leishmania is not well characterized. Here, we report the cloning, expression, and characterization of the Rab1 homologue from Leishmania. We have found that LdRab1 localizes in Golgi in Leishmania. To understand the role of LdRab1 in the secretory pathway of Leishmania, we have generated transgenic parasites overexpressing GFP-LdRab1:WT, GFP-LdRab1:Q67L (a GTPase-deficient dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 60 publications
4
34
0
Order By: Relevance
“…However, how Ldgp63 exits from ER and follows the secretory pathway in the parasites is not known. Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, how Ldgp63 exits from ER and follows the secretory pathway in the parasites is not known. Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 93%
“…To understand the functions of Leishmania Sar1 more precisely, two mutants viz, GTP-locked (H74L) and GDP-locked (T34N) were generated by PCR mediated site directed mutagenesis using appropriately designed mutant primers as described previously (36). Briefly, megaprimer for H74L was generated using WT Sar1 forward primer and mutated reverse primer (5 / -GCCTGCTGAAGGCCACCCATATC-3 / ) by PCR and subsequently full length mutated product was generated using this megaprimer as forward primer with WT reverse primer.…”
Section: Generation and Purification Of Different Mutants Of Copii Prmentioning
confidence: 99%
See 3 more Smart Citations